2020
DOI: 10.3390/ijms21165684
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Gallic Acid and Its Distributions in Tea (Camellia sinensis) Plants at the Tissue and Subcellular Levels

Abstract: In tea (Camellia sinensis) plants, polyphenols are the representative metabolites and play important roles during their growth. Among tea polyphenols, catechins are extensively studied, while very little attention has been paid to other polyphenols such as gallic acid (GA) that occur in tea leaves with relatively high content. In this study, GA was able to be transformed into methyl gallate (MG), suggesting that GA is not only a precursor of catechins, but also can be transformed into other metabolites in tea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…The tea is made from the tender leaves of the tea plants ( Camellia sinensis (L.) O. Kuntze), and is one of the three most popular consumed nonalcoholic beverages. Previous studies focused on the relationships of tea metabolites with tea quality and function [ 55 57 ]. In this study, during the profuse flowering stage of intercropping soybean, the different metabolites were involved in the different metabolic pathways and and formed two complete metabolism network diagrams as the flavonoid compound metabolism and other all secondary metabolites metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The tea is made from the tender leaves of the tea plants ( Camellia sinensis (L.) O. Kuntze), and is one of the three most popular consumed nonalcoholic beverages. Previous studies focused on the relationships of tea metabolites with tea quality and function [ 55 57 ]. In this study, during the profuse flowering stage of intercropping soybean, the different metabolites were involved in the different metabolic pathways and and formed two complete metabolism network diagrams as the flavonoid compound metabolism and other all secondary metabolites metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Tea plants are a species, among others, that contain abundant secondary metabolites [ 8 , 10 , 14 ]. Many studies have used this method to study the biosynthesis of secondary metabolites in tea plants [ 15 , 16 , 17 ]. In the present study, SA was found to be metabolized into SAG and MeSA in tea tissues using stable isotope tracing ( Figure 2 and Figure 3 ), consistent with SA metabolism in other species [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nonaqueous fractionation (NAF) method has been widely used to investigate the distribution of metabolites in many plant species [ 21 , 22 ]. Recently, NAF has been successfully applied in determining the characteristic metabolites from tea plants [ 15 , 23 ]. In the present study, the subcellular distributions of SA and SAG was revealed by the NAF method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallic acid acts as an important contributor to plant taste (Zhou et al, 2020). While Liu et al (2013) isolated and identified gallic acid as an allelochemical.…”
Section: Discussionmentioning
confidence: 99%